2014
DOI: 10.2147/dhps.s68786
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of poor glycemic control in type 2 diabetic patients attending public hospitals in Dar es Salaam

Abstract: BackgroundTanzania has recently experienced a significant rise in the burden of diabetes, and it is estimated that more than 400,000 people are living with diabetes. A major concern in the management of diabetes is the occurrence of diabetic complications that occur as a result of poor glycemic control. Identification of the factors associated with poor glycemic control is important in order to institute appropriate interventions for the purpose of improving glycemic control and prevention of chronic complicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

32
104
10
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(151 citation statements)
references
References 34 publications
32
104
10
5
Order By: Relevance
“…However, they used low-density lipoprotein cholesterol (LDL-cholesterol) for lipid profile and HbA1c for glycemic control as well as a lower cutoff point for blood pressure assessment, which is different from us. In line with our finding, similar rate of poor glycemic control was reported from Tanzania (69.7%) [19]. However, we found slightly higher prevalence of poor glycemic control based on mean FPG (72.3%) and lower results according to HbA1c calculated from mean FPG (58.5%).…”
Section: Discussionsupporting
confidence: 92%
“…However, they used low-density lipoprotein cholesterol (LDL-cholesterol) for lipid profile and HbA1c for glycemic control as well as a lower cutoff point for blood pressure assessment, which is different from us. In line with our finding, similar rate of poor glycemic control was reported from Tanzania (69.7%) [19]. However, we found slightly higher prevalence of poor glycemic control based on mean FPG (72.3%) and lower results according to HbA1c calculated from mean FPG (58.5%).…”
Section: Discussionsupporting
confidence: 92%
“…About glycemic control, primordial in the prevention of chronic complications of diabetes, abnormal glucose was found in the study population, which support the data found in many studies performed with DM elderly [23,24].…”
Section: Discussionsupporting
confidence: 88%
“…An education program that emphasizes the importance of medication adherence, physical exercise and weight control would be a relevant basic benefit for improving glycemic control in this patients [24].…”
Section: Discussionmentioning
confidence: 99%
“…Self‐care behaviors are crucial to affect subsequent QoL. Cross‐sectional and longitudinal studies have also indicated self‐care behaviors are significantly negatively correlated with HbA1C levels (Egede, Gebregziabher, Echols, & Lynch, ; Kamuhabwa & Charles, ). In this work, however, the 6‐month self‐care behavior did not affect 12‐month HbA1C levels.…”
Section: Discussionmentioning
confidence: 99%